Durvalumab activity in previously treated patients who stopped durvalumab without disease progression. Issue 2 (26th August 2020) - Sheth, Siddharth; Gao, Chen; Mueller, Nancy; Angra, Natasha; Gupta, Ashok; Germa, Caroline; Martinez, Pablo; Soria, Jean-Charles
Abstract : Background: Limited data exist on potential clinical benefit with anti-programmed cell death ligand-1 (PD-L1) retreatment in patients who stop initial therapy for reasons other than disease progression or toxicity and develop disease progression while off treatment. Patients and methods: NCT01693562 was a phase I/II study evaluating durvalumab monotherapy in advanced solid tumors. Patients benefiting from treatment were taken off durvalumab at 1 year per protocol and prospectively followed. At disease progression, they were eligible for durvalumab retreatment. Outcomes evaluated during retreatment included best overall response (BOR2), duration of response (DoR2), disease control rate (DCR2), and progression-free survival (PFS2). Results: Of 980 patients enrolled and treated with durvalumab 10 mg/kg every 2 weeks (Q2W) in the dose-expansion cohorts, 168 completed 1 year of initial durvalumab treatment with confirmed BOR1 of complete response in 20 (11.9%), partial response (PR) in 84 (50%), stable disease (SD) in 52 (31%), and disease progression in 12 (7.1%). All 168 patients stopped treatment and were eligible for retreatment at progression; 70 patients (41.7%) representing 14 primary tumor types were retreated and response evaluable. Confirmed BOR2 was PR in 8 patients (11.4%), SD in 42 (60.0%), disease progression in 16 (22.9%), and unevaluable in 4 (5.7%). Median DoR2 was 16.5 months. DCR2 ≥24 weeks (DCR2 24) was 47.1%. PFS2 rate at 12 months was 34.2%, and median PFS2 was 5.9 months. Median overall survival (OS2) was 23.8 months. Response rates, DCR2 24, and median DoR2 were generally greater in patients with high PD-L1 expression than those with low/negative expression. No new safety signals were observed during retreatment. Conclusion: Retreatment restored antitumor activity, resulting in high rates of durable disease control with an acceptable safety profile. This evidence supports retreatment of patients who stop anti-PD-L1 therapy for reasons other than progression or toxicity, and supports further investigation.